Bibliometric analysis of scientific research about sexuality and dementia in the elderly (Bioscience Journal, 2020)
Map global scientific research on sexuality and dementia in the elderly to understand the focus and the growth of the area during the past decades. An exploratory study, descriptive and bibliometric with academic works on the database ISI Web of Knowledge/Web of ScienceTM. The following descriptors were used: “elder*”, “dementia*” and “sexuality*” in the time-based scratch between 1945 and 2018. The data analysis was performed with the aid of the software HistCiteTM. After applied the filters of refinement, there were identified 79 articles, published in 45 different journals indexed in the database in reference, written by 157 authors linked to 96 research institutions located in 19 countries. To achieve these articles there were used 2,312 references with an average of approximately 32 references per article. The international scientific production about sexuality and dementia in the elderly is scarce, and highlights the need for more specific studies on the theme and its potential for exploitation in future studies.